Microphotometric quantitation of succinic dehydrogenase in whole isolated osteoclasts - Martin, C. I.; Itoiz, María Elina; Ubios, Angela M. (1986)
Fil: Martin, C. I. Comisión Nacional de Energía Atómica; Argentina